2020
DOI: 10.1042/bcj20200298
|View full text |Cite
|
Sign up to set email alerts
|

Thermogenic adipocytes: lineage, function and therapeutic potential

Abstract: Metabolic inflexibility, defined as the inability to respond or adapt to metabolic demand, is now recognised as a driving factor behind many pathologies associated with obesity and the metabolic syndrome. Adipose tissue plays a pivotal role in the ability of an organism to sense, adapt to and counteract environmental changes. It provides a buffer in times of nutrient excess, a fuel reserve during starvation and the ability to resist cold-stress through non-shivering thermogenesis. Recent advances in single-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 273 publications
(404 reference statements)
0
14
0
1
Order By: Relevance
“…Since then, many studies have found distinct adipocyte progenitor cells with various cell surface proteins expressed in WAT [ 128 ] and, recently, single-cell RNA sequencing (scRNAseq) technology was used to find new gene markers able to better define the cellular subpopulation involved in adipogenesis (reviewed in [ 130 , 131 ]). This new way to search for new markers led David Merrick et al [ 45 ] to identify distinct types of progenitor cells in murine subcutaneous adipose tissue, which were subdivided into three hierarchical groups based on their gene expression patterns (reviewed in [ 132 , 133 ]). The first population, termed “interstitial progenitor cells” (IPCs), is highly proliferative and undifferentiated.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, many studies have found distinct adipocyte progenitor cells with various cell surface proteins expressed in WAT [ 128 ] and, recently, single-cell RNA sequencing (scRNAseq) technology was used to find new gene markers able to better define the cellular subpopulation involved in adipogenesis (reviewed in [ 130 , 131 ]). This new way to search for new markers led David Merrick et al [ 45 ] to identify distinct types of progenitor cells in murine subcutaneous adipose tissue, which were subdivided into three hierarchical groups based on their gene expression patterns (reviewed in [ 132 , 133 ]). The first population, termed “interstitial progenitor cells” (IPCs), is highly proliferative and undifferentiated.…”
Section: Discussionmentioning
confidence: 99%
“…В результате образуются СЖК, служащие основным субстратом термогенеза. Помимо внутриклеточного пула ТГ, термогенные адипоциты используют в качестве источника энергии циркулирующие в сосудистом русле липиды, аминокислоты, а также глюкозу, на долю которой в качестве энергетического субстрата приходится до 10% [44]. Адренергическая стимуляция с вовлечением цАМФ повышает транскрипцию ГЛЮТ1 и способствует его транслокации к клеточной мембране, в то время как инсулин путем воздействия на фосфатидилинозитол-3-киназу индуцирует транслокацию ГЛЮТ4.…”
Section: развитие адипогенезunclassified
“…White adipocytes are responsible for storing triacylglycerides (TGs). The brown adipocytes use lipids to produce heat in part through a UCP-1 associated uncoupling of electron transport from ATP production (Pollard and Carling, 2020). Beige adipocytes (“brown-like”) can also support UCP1-independent thermogenesis (Pollard and Carling, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The brown adipocytes use lipids to produce heat in part through a UCP-1 associated uncoupling of electron transport from ATP production (Pollard and Carling, 2020). Beige adipocytes (“brown-like”) can also support UCP1-independent thermogenesis (Pollard and Carling, 2020). These beige cells arise within white fat pads in response to activators such as cold exposure (Jiang et al, 2017), b3-adrenergic receptor (Adrb3) agonists (Lee et al, 2013b), PPARg ligands (Wang et al, 2016), cancer cachexia (Kir et al, 2014), and exercise training (Chouchani et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation